Efficient Synthesis of 5-Trifluoromethylthio-1,2,3-Triazoles: One-Pot Multicomponent Reaction from Elemental Sulfur and TMSCF3 - Zhang, Lin-Lin; Li, Meng-Tian; Shen, Liang-Liang; Wu, Qin-Pei (Synthesis, 2020)
A sequential multistep reaction toward 5-trifluoromethylthio-1,2,3-triazoles has been established, starting from alkynes, organoazides, S8, and (trifluoromethyl)trimethylsilane (TMSCF3). This reaction features mild conditions, easy operation, and readily available substrates.
Keywords: copper iodide; sulfur; triazole; (trifluoromethyl)trimethylsilane; multicomponent reaction